PENGELOLAAN PENDIDIKAN KARAKTER DALAM PENGEMBANGAN SOFT SKILL SISWA - Noni, Noni; Marsyitah, Iis; Sisdiana, Etty (Research and Development Journal of Education, 2024)
This study aims to determine: 1) the concept of character education in the development of soft skills, 2) the implementation of character education in the development of soft skills, and 3) the supporting and inhibiting factors of character education in the development of soft skills. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The validity tests of the data include credibility, transferability, dependability, and confirmability. The data were analyzed using the triangulation method, which includes data reduction, data presentation, and drawing conclusions. The results of this study are: 1) the concept of character education in the development of students' soft skills uses the concept of role modeling, 2) the implementation of character education in the development of students' soft skills includes 18 character values in learning, plus the values of discipline, environmental care, cleanliness, and social concern in the Waste Bank Program, and 3) the supporting and inhibiting factors of character education in the development of soft skills include: (a) a conducive situation, (b) pre-programmed activities, (c) supportive facilities and infrastructure, (d) good human resources, leadership, and teacher role models. The inhibiting factors include: (a) lack of communication between the school and parents, (b) students' lack of awareness, and (c) differing understandings among school members about character education and soft skills development.